2017
DOI: 10.1111/oik.04587
|View full text |Cite
|
Sign up to set email alerts
|

A framework for understanding human‐driven vegetation change

Abstract: Despite a major research focus on human‐mediated reshuffling of plant communities, no coherent framework unites the numerous types of changes in abundances and distributions of native and non‐native species that are driven by human activities. Human driven vegetation change can occur through: non‐native species introductions; population outbreaks or collapses; range expansions or contractions; and range shifts of both native and non‐native species. Boundaries among these different types of floristic changes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 126 publications
0
15
0
Order By: Relevance
“…The most evident effect of plant invasions is the loss of local plant community composition and diversity (Callaway and Aschehoug, 2000;Cutway, 2017) through different mechanisms such as competition for limited resources, exploitation of resources untapped by local vegetation, novel chemical compounds and biotic interactions (Levine et al, 2003;Pyšek et al, 2012, Lorenzo et al, 2013. Loss of native diversity and domination of invasive plant species have been found to reduce provisioning and regulating ecosystem services, such as water provision, wildfire regulation, plant biodiversity and soil stabilization (Callaway and Aschehoug, 2000;Pyšek et al, 2012;Inderjit et al, 2017). Different mechanisms by which invasive plant species influence aboveground vegetation have been studied in detail (Simberloff et al, 2013;Inderjit et al, 2017) but the related below-ground ecosystem processes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most evident effect of plant invasions is the loss of local plant community composition and diversity (Callaway and Aschehoug, 2000;Cutway, 2017) through different mechanisms such as competition for limited resources, exploitation of resources untapped by local vegetation, novel chemical compounds and biotic interactions (Levine et al, 2003;Pyšek et al, 2012, Lorenzo et al, 2013. Loss of native diversity and domination of invasive plant species have been found to reduce provisioning and regulating ecosystem services, such as water provision, wildfire regulation, plant biodiversity and soil stabilization (Callaway and Aschehoug, 2000;Pyšek et al, 2012;Inderjit et al, 2017). Different mechanisms by which invasive plant species influence aboveground vegetation have been studied in detail (Simberloff et al, 2013;Inderjit et al, 2017) but the related below-ground ecosystem processes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of native diversity and domination of invasive plant species have been found to reduce provisioning and regulating ecosystem services, such as water provision, wildfire regulation, plant biodiversity and soil stabilization (Callaway and Aschehoug, 2000;Pyšek et al, 2012;Inderjit et al, 2017). Different mechanisms by which invasive plant species influence aboveground vegetation have been studied in detail (Simberloff et al, 2013;Inderjit et al, 2017) but the related below-ground ecosystem processes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the hypotheses that are currently debated in invasion ecology assume that species experience biogeographical-evolutionary advantages in their introduced ranges compared to their native ranges (Hierro, Maron, & Callaway, 2005;Inderjit, Catford, Kalisz, Simberloff, & Wardle, 2017;Inderjit, Wardle, Karban, & Callaway, 2011). Gallien et al (2016) reported that understanding biogeographical and evolutionary histories is valuable for understanding pine invasions.…”
Section: Biogeographical-evolutionary Advantagesmentioning
confidence: 99%